2019
DOI: 10.1080/10717544.2019.1662514
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical generation of microbubbles by carbon nanotube interdigital electrodes to increase the permeability and material uptakes of cancer cells

Abstract: Artificial cavitation as a prerequisite of sonoporation, plays an important role on the ultrasound (US) assisted drug delivery systems. In this study, we have proposed a new method of microbubble (MB) generation by local electrolysis of the medium. An integrated interdigital array of three-electrode system was designed and patterned on a nickel-coated quartz substrate and then, a short DC electrical pulse was applied that consequently resulted in distributed generation of microbubbles at the periphery of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Nourbakhsh et al demonstrated the effect of MDSC in autoimmune and its therapeutic application [37]. Khayamian et al investigated the increase in cancer cell permeability and material absorption [38]. It demonstrates the benefit of our technique in offering a valuable tool for breast cancer multi-classification in healthcare situations while reducing the expense of complex annotation [39].…”
Section: Literature Reviewmentioning
confidence: 91%
“…Nourbakhsh et al demonstrated the effect of MDSC in autoimmune and its therapeutic application [37]. Khayamian et al investigated the increase in cancer cell permeability and material absorption [38]. It demonstrates the benefit of our technique in offering a valuable tool for breast cancer multi-classification in healthcare situations while reducing the expense of complex annotation [39].…”
Section: Literature Reviewmentioning
confidence: 91%
“…CD8 and CD19 expression in PBMCs was assessed using inverted fluorescence microscopy. As previously reported by our group ( Ansaryan et al, 2019 ; Khayamian et al, 2019 ), the PBMCs were first fixed in 3.7% formaldehyde for 15 min and permeabilized with Triton X-100 in PBS for 5–10 min (with a concentration of 1%) at room temperature. The cells were then washed with PBS and then treated with a blocking buffer (1% BSA in PBS) for 40 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…3.2 EIS analysis of the cytokine storm in the patient samples 3.2.1 Device characterization and molecular dynamics simulation. In order to test the blood serum, three prevalent types of electrode materials [51][52][53][54][55] including gold (Au), carbon and graphene were candidates for EIS analysis. Adhesion and spread of the serum on the selected substrates were evaluated by the contact angle method.…”
Section: Cytokine Analysis Of the Serum Samples By Elisamentioning
confidence: 99%